UJI KINERJA TUNGKU PANGGGANGAN - Asep Irawan; Budianto Lanya (The University of Lampung, 2016)
The purpose of barbequing is to cookfood and provide a distinctive smoke aroma. This research aims at testingandperforming of a furnace grill. Thefurnace grill was fabricated with main components including combustionchamber, roasting rack, nozzlepipe, and a blower. Thegrill was designed with a roasting rack of 1800 cm 2 and hada capacity of 16 piece of chicken parts.Grill testing was conducted with and without roasting load.The parameterto observing included fuel capacity, roasting temperature, weight loss, amount of fuel consumption, airconsumption, and roasting duration. Results using coconut shell charcoal showed that the grill working goodwith roasting temperature of 416.3 o C. The grill had a fuel capacity of 2 kg with coconut shell charcoal and airconsumption of 25.44 kg. The roasting capacity was 16 pieces of chicken breast and was 16 pieces of chicken leg.The average roasting duration was 4.84 minuteswith 2.3 minutespausefor preparation and serving. Workingcapacity of the grill was 144 pieces per hour for chicken breast and 142pieces per hour for leg. Average weightloss was 20.5% and 11.3% for chicken breast and chicken leg, respectively. Fuel consumption for each roastingprocess was 395.5gram ofcoconut shell charcoal, equivalent to 13.441 kJ. Electric power consumption was150.13 kJ for each roasting process.Keywords:Furnace grill, design, performance, charcoal, cost.